ARCTIC RUBBER - Honn, F. J.; Hoyt, J. M. (1953)
Pilot studies and large scale evaluations were made of the more promising elastomers, with special emphasis on the polymer designated as X-300 rubber. Additional monomer, copolymer and rubberlike systems were made available for study. Of the 3 additional vulcanizing agents investigated, suring agent 180-56 appears promising. A 5-lb sample of 30/70 and a 15-lb sample of 42/58 molar CF2=CFCl/CF2=CH2 along with a 0.5-lb sample of approximately 43/54/4 molar CF2=CFCl/CF2=CH2/CF3-CF=CF2 terpolymer were submitted for testing. Recipes and operating procedures for the X-300 pre-pilot plant were studied, and progress was made toward establishing better control of the polymerization. The prepilot plant produced 272 lb of X-300. A rapid method was devised for comparing the low temperature and oil-resistance properties of small samples of raw, rubbery polymers.